What Multiple Myeloma With t(11;14) Should Be Classified Into in Novel Agent Era: Standard or Intermediate Risk? - Gao, Wen; Du, Juan; Liu, Junru; Zhou, Huixing; Zhang, Zhiyao; Jian, Yuan; Yang, Guangzhong; Wang, Guorong; Tian, Ying; Li, Yanchen; Wu, Yin; Fu, Weijun; et al. (Frontiers in Oncology, 2020)
Objective: To investigate the prognostic value of t(11;14) for de novo multiple myeloma (MM) patients in novel agent era. Methods: 455 patients, with fluorescence in situ hybridization (FISH) before treatments from three hospitals in China, were included in the study. All patients received autologous stem cell transplantation (ASCT) after induction therapy as consolidation. High risk (HR) cytogenetics were defined as t(4;14), t(14;16), and/or del 17p. Results: 152 patients were in the HR group. Of patients without HR cytogenetics, 55 were in the t(11;14) group, and 248 in the standard risk (SR) group without t(11;14). 1q21 gain was observed in 38.9% patients with t(11;14). There were no differences in median progression free survival (PFS) and overall survival (OS) respectively between patients in t(11;14) group and those in SR group. Patients in t(11;14) group had the longer median PFS and OS respectively compared with those in HR group. Regardless of coexisting with1q21 gain or not, patients in t(11;14) group still had the similar median PFS and OS compared to those in SR group. Finally, multivariate analysis indicated that including 1q21 gain and bone marrow plasm cell with CD20 expression, no variables were found to predict the outcome of t (11;14) group in our cohort. Conclusions: These results confirm that outcomes of t(11;14) MM are similar to standard risk patients when they receive novel agent induction therapy consolidated by ASCT. 1q21 gain coexists with t (11;14) frequently. In addition, both bone marrow plasm cell with CD20 expression and 1q21 gain have no impact on median PFS or OS for patients with t (11;14).